1970
DOI: 10.1002/ajpa.1330320106
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of forks in epidermal‐ridge minutiae in the finger print

Abstract: The frequency of minutia types was studied in finger prints of 77 males and 82 females. Dermal ridges were clearly printed by a revised method for this purpose.The fork index, which represents the frequency of forks in minutiae, is higher in females for each finger than in males. It differs on each finger, i.e., low on the digit I, high on the digits, 111, IV and V, and intermediate on the digit 11. The mean of the index for each finger distributes from about 15 to 24. Bilateral difference is not evident. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
3
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 2 publications
0
18
3
1
Order By: Relevance
“…Moore 13 also carried out a study on ridge to ridge distance and found that mean distance is more in male compared to female, but he studied only 10 males and 10 females. Okajima 14 also found that fork index is higher in females than in male in fingerprints. This again upholds the trend as in this present study.…”
Section: Discussionmentioning
confidence: 92%
“…Moore 13 also carried out a study on ridge to ridge distance and found that mean distance is more in male compared to female, but he studied only 10 males and 10 females. Okajima 14 also found that fork index is higher in females than in male in fingerprints. This again upholds the trend as in this present study.…”
Section: Discussionmentioning
confidence: 92%
“…Cummins and Midlo (1943) have established that females do have higher mean ridge count (23.4) than males (20.7). Okajima (1970) also found that fork index is higher in females than in male in fingerprints. This again upholds the trend as in this present study.…”
Section: Calculation Of Minutiae Characteristics With Respect To Genementioning
confidence: 83%
“…However, other features such as minutiae and epidermal ridge width (ridge density) have not been generally studied more in comparison to the feature mentioned above, despite being features of considerable significance due to their direct relevance in personal identification. Okajima (1970) studied the basic minutiae present in the prints taken from twins belonging to various populations and noted higher correlations between the numbers of minutiae present in the prints of monozygotic and dizygotic twins. More minutiae were observed in prints from males as compared to females, but no bilateral differences (right vs. left) have been observed (Okajima 1970).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minutiae density was determined within a circle whose diameter cuts 18 ridges, and passing through the nucleus of the fingerprints as described in the previous methods (Okajima 1970;Adamu et al 2017). Nine types of minutiae bifurcation, convergent, ridge ending, ridge enclosure (small), ridge enclosure (big), ridge fragment (small), ridge fragment (big), ridge dot between the ridges and dot within the ridges as defined by previous workers (Gutierrez-Redomero et al 2007;Adamu et al 2017) were narrowed to five types, ridge bifurcation (bifurcation& convergence), ridge ending, ridge enclosure (small & big), short ridge (small and big fragments), ridge dot (dot between or within the ridges).The selection of five minutiae types in this study was based on their distinctive characteristics and they are frequently encountered in comparison of fingerprints by forensic expert (Fournier and Ross 2016).…”
Section: Minutiae Counts and Classificationmentioning
confidence: 99%